2017
DOI: 10.1186/s12868-017-0400-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vitamin D administration on brain inflammatory markers in high fat diet induced obese rats

Abstract: BackgroundObesity induced brain inflammation is associated with cognitive disorders. We aimed to investigate the influence of vitamin D on hypothalamus and hippocampus inflammatory response in high-fat diet induced obese rats.MethodsIn the beginning of the study, 40 rats were divided into two groups: control diet and high fat diet (HFD) for 16 weeks; then each group subdivided into two groups including: N, ND + vitamin D, HFD and HFD + vitamin D. Vitamin D supplementation was done for 5 weeks at 500 IU/kg dosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 54 publications
4
20
0
Order By: Relevance
“…The association between vitamin D and mental health was so far studied mainly for depression or depressive symptoms [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ] and some potential mechanisms explaining the influence of vitamin D were supposed [ 64 ]. Vitamin D has potential to cross the blood-brain barrier, to activate receptors in brain cells and to exert its direct impact in the central nervous system [ 65 ]. Moreover, there is some evidence for the link between vitamin D and Vitamin D Receptors (VDRs) and the regulation of human behavior, that is strongly suggested by the presence of VDRs in such brain areas as cortex, cerebellum and limbic system [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between vitamin D and mental health was so far studied mainly for depression or depressive symptoms [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ] and some potential mechanisms explaining the influence of vitamin D were supposed [ 64 ]. Vitamin D has potential to cross the blood-brain barrier, to activate receptors in brain cells and to exert its direct impact in the central nervous system [ 65 ]. Moreover, there is some evidence for the link between vitamin D and Vitamin D Receptors (VDRs) and the regulation of human behavior, that is strongly suggested by the presence of VDRs in such brain areas as cortex, cerebellum and limbic system [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies in animal models indicated potential anti-inflammatory effects of vitamin D administration in hippocampus and hypothalamus and its modulating effects on brain-derived neurotropic factor (BDNF) [ 65 ] which may also play a role. Simultaneously, the role of vitamin D may be attributed to its neuroprotective role in the brain which is reflected in modulating neurotrophic signaling [ 69 ], and in regulating inflammation by inhibiting proinflammatory cytokines [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rats were then categorized into four groups (six rats/each). The first one received no treatment (only CCT diet) and referred to as a control group or diabetic hyperlipidemic control (DHC) group), group 2 received 10-DHGD (extracted from ginger fresh rhizomes ( Zingiber officinale ) 10 mg/kg orally, 31,49 group 3 received vitamin D3 (the Medical Union of Pharmaceuticals (MUP, Egypt)) 500 IU/kg weekly administered by oral gavage, 5052 group 4 received a combination therapy of 10-dehydrogingerdione and vitamin D3. Another group of normal rats (group 5) that received only chow diet was included and referred to normal group.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies showed an increased cytokine production, including interleukin-1β (IL-1β), interleukin-6 (IL-6), monocyte chemoattractant protein-1 (MCP-1), and tumor necrosis factor alpha (TNF-α), in HT patients [ 25 , 26 ]. Vitamin D has been involved in modulating the secretion of cytokines, including TNF-α, IL-6, IL-1β, and MCP-1 [ 27 – 29 ]. Numerous studies support the notion that inflammation, characterized by elevated cytokines, play a pivotal role in the pathogenesis of cognitive impairment [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%